THE EFFECTIVENESS OF CORETAX IMPLEMENTATION ON TAXPAYERS THROUGH A HUMANISTIC AND VALUE-BASED GOVERNANCE APPROACH: A CRITICAL PARADIGM FRAMEWORK - Diah Rizkyan Dewi; Rien Agustin Fadjarenie (ZILLZELL MEDIA PRIMA, 2026)
Indonesian taxation has undergone continuous reforms since 1984. It is currently in the digital transformation stage, with the Core Tax Administration System (CTAS) representing a significant initiative to digitalize tax governance. The Coretax system, as an integrated digital platform, aims to enhance the effectiveness of implementing taxpayers’ rights and obligations by automating registration, reporting, and payment procedures. Within the framework of value-based governance, this study explores how the implementation of Coretax aligns technological efficiency with humanistic values to strengthen trust, transparency, and compliance. Using a qualitative approach within a critical paradigm, this research analyzes the effectiveness of Coretax implementation from the perspective of taxpayers and tax authorities. Primary data were collected from ten informants, including representatives from the Directorate General of Taxes, corporate and individual taxpayers, and tax consultants. Data were processed using NVivo 14 to identify contextual relationships between system readiness, socialization, and humanistic value orientation. The findings reveal that the implementation of Coretax has not yet been fully effective—both in socialization and system substance—due to the limited integration of humanistic and value-based elements in policy communication and system design. The novelty of this study lies in integrating a humanistic perspective into the framework of value-based governance to assess digital fiscal transformation, offering an alternative lens for evaluating the effectiveness of Indonesia’s tax reform policies. This study highlights the need for a governance model that harmonizes digital transformation with ethical and human-centered public service values to ensure equitable taxpayer participation and sustainable fiscal reform.